Achieving Large‐Area Planar Perovskite Solar Cells by Introducing an Interfacial Compatibilizer. Issue 22 (10th April 2017) - Lee, Jinho; Kang, Hongkyu; Kim, Geunjin; Back, Hyungcheol; Kim, Junghwan; Hong, Soonil; Park, Byoungwook; Lee, Eunhag; Lee, Kwanghee
Abstract : Despite the recent unprecedented increase in the power conversion efficiencies (PCEs) of small‐area devices (≤0.1 cm 2 ), the PCEs deteriorate drastically for PSCs of larger areas because of the incomplete film coverage caused by the dewetting of the hydrophilic perovskite precursor solutions on the hydrophobic organic charge‐transport layers (CTLs). Here, an innovative method of fabricating scalable PSCs on all types of organic CTLs is reported. By introducing an amphiphilic conjugated polyelectrolyte as an interfacial compatibilizer, fabricating uniform perovskite films on large‐area substrates (18.4 cm 2 ) and PSCs with the total active area of 6 cm 2 (1 cm 2 × 6 unit cells) via a single‐turn solution process is successfully demonstrated. All of the unit cells exhibit highly uniform PCEs of 16.1 ± 0.9% (best PCE of 17%), which is the highest value for printable PSCs with a total active area larger than 1 cm 2 . Abstract : Large‐area planar perovskite solar cells (PSCs) are demonstrated by an innovative method using an amphiphilic conjugated polyelectrolyte as an interfacial compatibilizer between the hydrophobic organic charge‐transport layer and hydrophilic perovskite layer. Highly scalable PSCs with uniform perovskite films on a large‐area substrate (18.4 cm 2 ) and with an active area of 1 cm 2 exhibit stabilized power conversion efficiencies of 17%.